Graphene and zeolite as adsorbents in bar-micro-solid phase extraction of pharmaceutical compounds of diverse polarities - Maizatul Najwa Jajuli (Tanjung Malim, 2021)
Graphene and zeolite as adsorbents in bar-micro-solid phase extraction of pharmaceutical compounds of diverse polarities by Maizatul Najwa Jajuli